2014
DOI: 10.1371/journal.pone.0112851
|View full text |Cite
|
Sign up to set email alerts
|

Transient Exposure to Ethanol during Zebrafish Embryogenesis Results in Defects in Neuronal Differentiation: An Alternative Model System to Study FASD

Abstract: BackgroundThe exposure of the human embryo to ethanol results in a spectrum of disorders involving multiple organ systems, including the impairment of the development of the central nervous system (CNS). In spite of the importance for human health, the molecular basis of prenatal ethanol exposure remains poorly understood, mainly to the difficulty of sample collection. Zebrafish is now emerging as a powerful organism for the modeling and the study of human diseases. In this work, we have assessed the sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 66 publications
4
29
0
Order By: Relevance
“…With regard to pax2a , our data confirm earlier studies that showed this MHB marker was not affected by early ethanol exposure (Coffey et al, 2013; Joya et al, 2014), although Coffey et al (2013) showed decreased pax2 a expression following later exposure to ethanol. Pax2a MHB expression was only lost in a small subset of aldh1a3 morphants and in fgf8a morphants in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…With regard to pax2a , our data confirm earlier studies that showed this MHB marker was not affected by early ethanol exposure (Coffey et al, 2013; Joya et al, 2014), although Coffey et al (2013) showed decreased pax2 a expression following later exposure to ethanol. Pax2a MHB expression was only lost in a small subset of aldh1a3 morphants and in fgf8a morphants in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…These effects, evident in the anterior and posterior regions of the hypothalamus, are induced by both concentrations of ethanol, 0.25% and 0.5%. While neurogenesis in the brain of zebrafish has yet to examined in fish exposed as embryos to low concentrations of ethanol, moderate to high ethanol concentrations have been tested and found to have very different effects in fish, causing an increase in cell death and morphological malformations in the brain and also a decrease in neuronal differentiation in the spinal cord [58, 59]. Thus, the concentration of ethanol during embryonic development is critical for the outcome, with low concentrations stimulating neurogenesis in the hypothalamus as demonstrated here in larval zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large number of transgenic backgrounds available, new insights are being gained into how ethanol disrupts neural development in zebrafish. Exposure to 1% ethanol reduces the number of elavl3-positive neural progenitors 54 and 100 mM (0.6%) increases the branching of secondary motor neurons and decreased the diameter of Mauthner axons. 55 In addition, Zhang et al 56 reported that 0.5% ethanol exposure leads to disruption of the mid-hindbrain boundary.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 99%